Renewable Energy and Inclusive Economic Development: An African Case Study - Yuni, Denis Nfor; Ezenwa, Ndubuisi; Urama , Nathaniel E.; Tingum, Ernest Ngeh; Mohlori-Sepamo, Khothalo (International Journal of Sustainable Energy Planning and Management, 2023)
Climate change constitutes a major challenge to economic growth and development across the globe as it negatively affects most sectors of the economy. Hence, there has been a global clamour for countries to invest in climate change mitigations. In developing regions like Africa, however, there are high resource limitations, and as such, there is a general opinion that funding climate change mitigation will have a huge opportunity cost of low investment in other development infrastructures, with the likelihood of decreasing economic development. On this premise, this study investigates the impact of renewable energy consumption and output on economic development in Africa. The study employed panel data analysis estimated using the System Generalised Method of Moments for a sample of 43 Sub-Saharan African countries. The results show that an increased share of renewable electricity in total electricity production increased significantly and contributed positively to economic development in Africa. Also, the ratio of renewable electricity to the total electricity consumed had a positive but insignificant effect on economic development. The study thus concludes that an increase in renewable electricity production and consumption does not only mitigate climate change but could also contribute marginally to the economic growth and development of African economies.